Surface characterization of commercial chitosan with SEM and BET techniques - Kaya, Fatih; Taşar, Şeyda; Özer, Ahmet (Fırat University, 2022)
Chitosan, a natural polymer, has recently been the focus of attention of researchers due to its superior properties such as biocompatible, biodegradable, renewable, and low toxicity. Especially in the fields of chemistry and health sciences, its use as a wound dressing material, adsorbent, resin, drug carrier system, and food packaging is being researched. This study, it is aimed to contribute to the areas where chitosan is used as adsorbent, resin, and wound dressing material by making surface characterization. According to the data obtained from the study, it was determined that chitosan was a non-porous polymer with a membranous surface. In addition, it was determined that there may be calcium particles as a surface impurity on the surface of commercial chitosan samples.
Keywords: Chemical Engineering; Kimya Mühendisliği